ONE OF THE APPROACHES TO SOLVE THE PROBLEM OF THE COST OF A PHASE TRANSITION HEAT ACCUMULATOR FOR A SOLAR HEAT SUPPLY SYSTEM - Vladimirovna, Umerenkova Elina (Journal of Applied Engineering Science, 2021)
Based on the analysis of the Russian market of basic materials for phase-shifting heat accumulators (FPAT), including the issue of pricing policy, an attempt was made to reveal the dependence of the cost of a heat accumulator for a solar thermal supply system on operating and design parameters. In turn, to determine the latter, the method was used, which makes it possible to design FPAT with given design and technological parameters, at a given minimum temperature of the coolant at the outlet of the accumulator, the known thermophysical characteristics of the coolant and heat storage material (TAM), including the phase transition temperature
Keywords: solar systems; heat supply; phase transition heat accumulator; heat accumulating material